Portugal : Eighth and Ninth Reviews Under the Extended Arrangement and Request for Waivers of Applicability of End-September Performance Criteria. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Portugal's Eighth and Ninth Reviews Under the Extended Arrangement and Request for Waivers of Applicability of end-September Performance Criteria (PC). Program implementation has remained broadly on track, in spite of a political crisis and significant legal challenges. The medium term outlook remains broadly unchanged, with growth gradually increasing to near its underlying potential of 2 percent by 2017. The contribution from the net foreign balance is now projected to be some 0.2 percentage point higher over the medium term. The IMF Staff supports the authorities' request for completion of the combined eighth and ninth reviews and for waivers of applicability of the end-September PCs.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet